English(es) for Indonesians: A Review on Literatures - Anita Dewi (Universitas Bunda Mulia, 2017)
This paper investigates which English(es) should be learned by Indonesians, as the language has uncontrollably spread into the country. Divided into several sections - English in Indonesia Across Time, English’ Role for Indonesians, Inquiring English and National Identity, and The English Language(s) for Indonesians, and Final Remarks, this paper explores facts and realities of English existence inIndonesia. In order to provide a meaningful outcome, this paper concludes with some alternative thoughts of possible English(es) to be learned. Indeed, instead of leading to a “one-size-fits-all” solution for English learning inIndonesia, it is considered to be more sensible to leave the readers with more insights for further discussions. Keywords: English, Learning, Indonesia